The development and evaluation of a computer-based resource to enhance the education of pre-registration nursing students regarding knowledge and attitudes towards pain management - Keefe, Gemma (2011)
The study is the first in its field to quantitatively explore the effects of e-learning to improve knowledge and attitudes towards pain management. Pain is a fundamental reason for patients seeking healthcare, yet in recent years it has been acknowledged that the importance of pain management is often overlooked or misunderstood, with poor pain education frequently blamed. In fact, the extent of pain education is severely limited in current nursing curricula, primarily due to a lack of prioritisation of pain, but with a new consultation underway to add pain to the NHS Essence of Care Benchmarks, there may soon be little option but for nursing schools to implement improved and consistent education regarding pain management.